Seafloor Map of the Alghero Bay (Sardinia, Italy). Issue 2 (9th December 2020) - De Luca, Mario; Chaiallah, Abdesslam; Andreucci, Stefano; Cossu, Giulia; Santonastaso, Antonio; Sechi, Daniele; Stelletti, Myriam; Pascucci, Vincenzo
ABSTRACT: The Alghero Bay is a coastal area of high economic value because of the presence of one of the most popular beaches of Sardinia (San Giovanni, Maria Pia, Le Bombarde, Lazzaretto). The organisms living in the meadow of Posidonia oceanica, which densely cover the offshore areas of the bay, represent the most important source of sediments to these beaches. For this reason, a detailed mapping of the local seabed features and distribution of P. oceanica constitutes an important tool for the coastal managing of the area. The integrated use of several methodologies, such as Side Scan Sonar, Remote Operating Vehicle, Drone and direct sediment sampling has allowed us to realize a very detailed seafloor map of the Alghero Bay.